2016
DOI: 10.7249/rr978
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for PTSD and Depression in the Military Health System: Phase I Report

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 34 publications
4
33
2
Order By: Relevance
“…These findings are somewhat inconsistent with the findings of other recent work. For example, a recent review of pharmacy data found that 31.5 percent of patients with depression received at least four medications over one observation year (Hepner et al, 2017), whereas our provider-reported data showed that 11.6 percent were currently prescribed four or more medications. This discrepancy may be due to a difference in measurement.…”
Section: Pharmacotherapy For Mddcontrasting
confidence: 61%
See 3 more Smart Citations
“…These findings are somewhat inconsistent with the findings of other recent work. For example, a recent review of pharmacy data found that 31.5 percent of patients with depression received at least four medications over one observation year (Hepner et al, 2017), whereas our provider-reported data showed that 11.6 percent were currently prescribed four or more medications. This discrepancy may be due to a difference in measurement.…”
Section: Pharmacotherapy For Mddcontrasting
confidence: 61%
“…This is consistent with the findings and recommendations of other recent work. For example, a recent review of pharmacy data found that 44.9 percent of service members diagnosed with PTSD received at least four medications over one observation year (Hepner et al, 2017). Differences by service were not significant (p = 0.55).…”
Section: Medication Management Within Mtfs Pharmacotherapy For Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…EBTs for mental health needs are not available in all health care settings (Tanielian and Jaycox, 2008). Although VHA has a number of quality measures and monitoring systems in place, DoD and civilian systems of care do not have robust performance-monitoring tools for quality improvement of mental health care (Burnam, Meredith, Tanielian, & Jaycox, 2009;Hepner et al, 2016;Hepner, Ferris, et al, 2017;Hepner, Sloss, et al, 2017). In addition, a recent RAND study on VA capacity found that, although VA health care quality fared well on many measures and domains compared with non-VA providers, quality performance was inconsistent across VA facilities, and quality improvement is needed in many areas (Hussey et al, 2015).…”
Section: Quality Of Carementioning
confidence: 99%